Bridging Tradition and Religion: Traditional Recitation (Pengajian Adat) in Kerinci - Haraska, Yola; Afrijulianti, Dina (Contemporary Society and Politics Journal, 2024)
This research focuses on the traditional recitations in Hiang Karya Village, known as the “three-village traditional recitation” (Hiang Karya, Hiang Tinggi, and Hiang Sakti). These recitations are typically studied by ninik mamak (traditional elders), syarak officials, village heads, and village staff from the three villages. The recitations are recognized as mixed traditional recitations, passed down through generations. Within this tradition, ninik mamak, syarak officials, village heads, village staff, and datok (former ninik mamak) learn the traditional and religious values embedded within them. Additionally, Hiang is home to a special recitation for women, known as the BKMT recitation (Badan Kontak Majelis Taklim). Hiang hosts a variety of recitations, not only those related to tradition within the traditional recitations but also those with profound religious significance. This study found that these recitations play a vital role in the lives of the Hiang community, both in preserving traditional customs and in strengthening Islamic values that serve as their guiding principles.